1990
DOI: 10.1002/1097-0142(19900201)65:3<433::aid-cncr2820650310>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy with cisplatin and 5-fluorouracil for penile and urethral squamous cell carcinomas

Abstract: Six men with either recurrent (n = 4) or unresectable (n = 2) squamous cell carcinoma of the penis (n = 5) and urethra (n = 1) received chemotherapy with cisplatin intravenously at a dose of 100 mg/m2. This was followed 24 hours later by a continuous intravenous infusion of 5-fluorouracil (5-FU) at a dose of 960 mg/m2/d for five days every 3 to 4 weeks. There was universal alopecia. The other toxicities were mild and consisted of mucositis, nausea, vomiting, reversible creatininemia, and transient azotemia. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(31 citation statements)
references
References 29 publications
2
27
0
2
Order By: Relevance
“…Hussein et al reported one complete response and five partial responses in six men with recurrent or unresectable squamous cell carcinoma of the penis [88]. Shammas et al treated eight patients with advanced squamous cell carcinoma of the penis, two of whom achieved a partial response, one requiring surgery and the other requiring surgery and radiotherapy to achieve a complete response [89].…”
Section: Advanced Disease (N3 Unresectable) or Metastatic At Presentmentioning
confidence: 96%
“…Hussein et al reported one complete response and five partial responses in six men with recurrent or unresectable squamous cell carcinoma of the penis [88]. Shammas et al treated eight patients with advanced squamous cell carcinoma of the penis, two of whom achieved a partial response, one requiring surgery and the other requiring surgery and radiotherapy to achieve a complete response [89].…”
Section: Advanced Disease (N3 Unresectable) or Metastatic At Presentmentioning
confidence: 96%
“…The disparity in survival rates has led to the addition of concurrent chemotherapy for proximal, higher stage lesions. A combination of radiation therapy and chemotherapy using 5-flurouracil and cisplatin has been shown to provide effective treatment for locally advanced urethral carcinoma in females (Hussein et al, 1990). A single institution study by Gheiler demonstrated the benefits of combination therapy, as 88% of patients treated with RT and concurrent 5-FU/cisplatin were alive NED at five years (Gheiler et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…However, a standard scheme of combination therapy is undefined. Hussein et al [16] reported that a novel chemotherapeutic combination (CDDP and 5-FU) achieved partial responses in five of six patients (five cases of penile cancer and one of SCC of the urethra). In SCC of the anus or larynx, combination therapy, multiagent chemotherapy, and surgery or radiation therapy resulted in improved outcomes [17,18].…”
Section: Discussionmentioning
confidence: 99%